Risk perception of educational communities in disaster-prone areas from the perspective of islamic educational psychology - Rofiq Faudy Akbar; Muhammad Miftah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to analyze the risk perception of educational communities situated within the Disaster-Prone Areas (Kawasan Rawan Bencana or KRB) of Mount Merapi, viewed through the lens of Islamic Educational Psychology. Risk perception is conceptualized not merely as a cognitive and emotional response to disaster threats, but as a psycho-spiritual construct shaped by Islamic values within educational practices. Utilizing a qualitative approach, this research conducted in-depth interviews with educators and institutional administrators in the sub-districts of Musuk and Kemalang (Central Java), and Cangkringan (Special Region of Yogyakarta). Data analysis was performed thematically, employing four primary dimensions of risk perception; exposure, familiarity, preventability, and dread which were further elaborated through key concepts of Islamic Educational Psychology, namely tazkiyat al-nafs (purification of the soul) consisting of; sabr (patience), tawakkal (reliance on God), and ikhtiar (proactive effort). The findings indicate that the risk perception of these educational communities is both adaptive and contextual, where disaster experiences cultivate a balance between rational vigilance and spiritual tranquillity. Furthermore, Islamic educational psychology values serve as psychological resources that bolster mental resilience, mitigate traumatic impacts, and foster educational practices more responsive to the psychosocial needs of students in disaster-prone regions. These findings underscore the critical importance of integrating Islamic Educational Psychology into the development of disaster education as a strategic framework for strengthening the resilience of educational communities.